Les voix de la liberté vivent : journaux des Alliés publies en Grande-Bretagne
Black and white photographs of members of the military reading newspapers, and of reproductions of covers of newspapers from various countries Suggested translation: The voices of freedom live : newspapers of Allies published in Great Britain PO-1263